2006
DOI: 10.1051/gse:2006011
|View full text |Cite
|
Sign up to set email alerts
|

Recording strategies and selection potential of feed intake measured using the X-ray method in rainbow trout

Abstract: This study examines the way long-term feed intake should be recorded accurately for selective breeding purposes, and estimates selection potential in feed intake using the X-ray method to record individual daily feed intake in rainbow trout (Oncorhynchus mykiss). The analysis showed that the point estimates of daily feed intake displayed low repeatabilities (r = 0.09–0.32). This indicates that a minimum of three repeated records were needed to accurately record average feed intake at a fixed age. To effectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 32 publications
(29 reference statements)
1
46
1
3
Order By: Relevance
“…Growth rate was correlated with feed intake but was not correlated with feed efficiency (FE), as FE reduces when consumption increases beyond a threshold level [11,21]. The inverse relationship observed between FE and white muscle protein concentration (not with body protein concentration) was probably due to a limited capacity to deposit muscle protein.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Growth rate was correlated with feed intake but was not correlated with feed efficiency (FE), as FE reduces when consumption increases beyond a threshold level [11,21]. The inverse relationship observed between FE and white muscle protein concentration (not with body protein concentration) was probably due to a limited capacity to deposit muscle protein.…”
Section: Discussionmentioning
confidence: 87%
“…It was purely intended to act as a challenge environment to optimising the genetic response of traits such as protein and growth efficiency in salmonids [21,22,27]. However, as a long-term study, it has enabled us to investigate the effect of dietary protein on skeletal growth (length), which is important knowledge for future production of fish with high growth performance quality [32] as well as for future growth study in natural ecosystems where protein deposition is the main cause [12].…”
Section: Discussionmentioning
confidence: 99%
“…Breeding programmes exist for all major farmed carnivorous fish species, and have achieved improvements in growth, feed efficiency, disease resistance and product quality traits [12]. Improved feed efficiency in particular is a goal of most fish breeding programmes, but genetic parameter estimates for feed consumption and efficiency are rare [21,22,24,42]. This is because recording methods for individual fish feed intake have only recently been implemented in large-scale genetics research [21,22,42]; thus no current breeding programmes select directly for feed efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…We also calculated the repeatability of the intake measurements as described in [20], where the repeatability, r = 1 À V Es /(V Es + V Eg ), V Es being the within-individual variance arising from repeated measurements and V Eg the between individual variance, the standard error was calculated as described by Becker [2].…”
Section: Validation Of X-ray Measurementsmentioning
confidence: 99%
“…It has been shown that feed intake of an individual fish within a group can be estimated from X-ray images of fish supplied with food containing a suitable dense marker [5,18,29]. The weakness of this approach is the low repeatability of estimated feed intake (from 0.09 to 0.32 in rainbow trout): a minimum of three repeated records seems to be necessary in order to buffer day-to-day variation and accurately describe the intake versus gain relationship [20]. However, even with five measurements, estimates of feed efficiency heritability remain low (6 ± 10%) [33].…”
Section: Introductionmentioning
confidence: 99%